Laboratory Performance Evaluation on the Recovering of Aged Bitumen With Vegetable Oil Rejuvenator - Suo, Zhi; Chen, Huan; Yan, Qiang; Tan, Yitian; Li, Xinghai; Zhang, Ao (Frontiers in Materials, 2021)
Generally, the conventional rejuvenators contains many mineral oils to supply the missing components of aged bitumen. The mineral oils could recover the performance of aged bitumen go through a long-term aging procedureprocess. However, the mineral oils are easy to volatilize at higher recycling temperature. The higher volatilization will reduce the effect of rejuvenator and limit proportion of reclaimed asphalt pavement (RAP) in recycled asphalt mixture (RAP contents less than 30%). The main components of vegetable oil are straight chain higher fatty acids and glycerides. The esters of straight chain higher fatty acids and glycerol are not volatile at high temperature. Therefore, they can be used to recover the aged bitumenmicro chemical composition of bitumen and a change in colloidal stability of asphaltene. according to the bitumen aging and rejuvenation theory. In this research, two newly kinds of bitumen rejuvenators were developed by replacing mineral oil with waste cooking corn and soybean oil. The two kinds of vegetable and a mineral bitumen rejuvenators were utilized to recover aged bitumen with 2 to 10% by weigh. The objectives of the research The DSR (Dynamic Shear Rheometer, AASHTO T315) and rotational viscosity tests (ASTM 4402) arewere conducted to evaluatinge the rheological properties, high temperature and fatigue performance of the recovered bitumen. The Dynamic Shear Rheometer Test and Rotational Viscosity Test were conducted according to the AASHTO and ASTM standards. Additionally, The the crack resistance of bitumen was evaluated by using the bending beam rheometer (BBR) test at -12 oC and -18 oC (AASHTO T313). The result of laboratory test and statistical analysis of ANOVA analysis showeds that the vegetable oil rejuvenators can more effectively reduce the viscosity and stiffness of aged bitumen. It will improve both the fatigue resistance and low temperature crack resistance of bitumen. In addition, when the content of vegetable oil is higher, the rejuvenating agent can make the recovered bitumen have lower viscosity and stiffness. Considering that the rutting resistance under high temperature, it is suggested that 6% and 8% vegetable oil be used to recover the aged bitumen.